Gene–Diet Interactions: Dietary Rescue of Metabolic Defects in spen-Depleted Drosophila melanogaster. Issue 4 (1st April 2020) - Gillette, Claire M; Hazegh, Kelsey E; Nemkov, Travis; Stefanoni, Davide; D'Alessandro, Angelo; Taliaferro, J Matthew; Reis, Tânia
Abstract: Obesity results from a complex interplay of diet, behavior, and genetic background. Our genes are out of our control, but it may be possible to customize our diet to match changes in metabolism resulting from... Obesity and its comorbidities are a growing health epidemic. Interactions between genetic background, the environment, and behavior ( i.e., diet) greatly influence organismal energy balance. Previously, we described obesogenic mutations in the gene Split ends (Spen) in Drosophila melanogaster, and roles for Spen in fat storage and metabolic state. Lipid catabolism is impaired in Spen -deficient fat storage cells, accompanied by a compensatory increase in glycolytic flux and protein catabolism. Here, we investigate gene–diet interactions to determine if diets supplemented with specific macronutrients can rescue metabolic dysfunction in Spen-depleted animals. We show that a high-yeast diet partially rescues adiposity and developmental defects. High sugar partially improves developmental timing as well as longevity of mated females. Gene–diet interactions were heavily influenced by developmental-stage-specific organismal needs: extra yeast provides benefits early in development (larval stages) but becomes detrimental in adulthood. High sugar confers benefits to Spen-depleted animals at both larval and adult stages, with the caveat of increased adiposity. A high-fat diet is detrimental according to all tested criteria, regardless of genotype. Whereas Spen depletion influenced phenotypic responses to supplemented diets, diet was the dominant factor in directing the whole-organism steady-state metabolome. Obesity is a complex disease of genetic, environmental, and behavioral inputs. Our results show that diet customization can ameliorate metabolic dysfunction underpinned by a genetic factor.